The histone variant H2A.W restricts heterochromatic crossovers in Arabidopsis - Namil Son; Heejin Kim; Jaeil Kim; Jihye Park; Dohwan Byun; Sang-jun Park; Hyein Kim; Yeong Mi Park; Pierre Bourguet; Frédéric Berger; Kyuha Choi (Proceedings of the National Academy of Sciences, 2025)
Meiotic crossovers rearrange allele combinations and create offspring diversity. Crossovers occur nonrandomly along chromosomes, predominantly in distal euchromatin and less in pericentromeric heterochromatin marked with histone H3 lysine 9 dimethylation (H3K9me2) and the H2A variant H2A.W in Arabidopsis thaliana . Loss of H3K9me2 increases heterochromatic crossovers, but how H2A.W affects crossover formation in pericentromeric regions is unknown. Here, we report that H2A.W is required to restrict heterochromatic crossovers in Arabidopsis . Using meiosis-specific microRNA-induced gene silencing (meiMIGS) and fluorescence-tagged recombination reporters, we show that meiotic knockdown of H2A.W.6 , H2A.W.7 , and H2A.W.12 ( meiMIGS-H2A.W.6/7/12 ) increases pericentromeric crossovers. High-resolution genomic maps of crossovers show that meiMIGS-H2A.W.6/7/12 enhances heterochromatic crossovers, similar to meiMIGS plants silencing the H3K9me2 pathway. Consistently, genome-wide crossover maps show that the mutants h2a.w.6 , h2a.w.7 , h2a.w.6 h2a.w.7 , and h2a.w.6 h2a.w.7 h2a.w.12, but not h2a.w.12, exhibit a similar increase in heterochromatic crossovers to meiMIGS-H2A.W.6/7/12 , demonstrating that H2A.W.6 and H2A.W.7 limit heterochromatic crossovers. Profiling of genome-wide nucleosome density using micrococcal nuclease sequencing reveals that h2a.w mutants with increased heterochromatic crossovers have increased heterochromatin accessibility, with lower H3K9me2 levels during meiosis. Our findings shed light on the role of H2A.W variants as heterochromatin compaction factors that suppress meiotic crossovers within the pericentromeric regions.